New routes for diaspora studies - Banerjee, Sukanya, 1973-; McGuinness, Aims, 1968-; McKay, Steven C. (Steven Charles) (21st Century studies., 2012)
Study of diasporas provides a useful frame for reimagining locations, movements, identities, and social formations. This volume explores diaspora as historical experience and as a category of analysis. Using case studies drawn from African and Asian diasporas and immigration in the U.S., the contributors interrogate ideas of displacement, return, and place of origin as they relate to diasporic identity. They also consider how practices of commensality become grounds for examining identity and difference and how narrative and aesthetic forms emerge through the context of diaspora.